Synthesis and Light Induced Characteristics of Siloxane Substituted Azobenzene: An Application for Optical Storage Device - Yuvaraj, A. R.; Lutfor, M. R.; M. M., Yusoff (Hindawi, 2016)
The light induced behaviour of siloxane substituted azobenzene compounds in the presence of alkylene spacers is reported for the first time. Firstly, these photosensitive compounds were synthesized and elucidated the molecular structure by spectral analysis such as NMR, FTIR, and UV/Vis. Photoisomerization effect was evaluated in solution and also in nematic phase. The photosaturation occurred exactly at 29 seconds, whereas thermal back relaxation was observed ranging from 19.8 to 23.8 hours. Long duration of the thermal back relaxation is due to the presence of sterically hindered siloxane group substituted to the azobenzene molecules. Decrease in the duration of cis-trans isomerization was found when the number of alkylene spacers was increased. These siloxane based azobenzene derivatives are useful for the fabrication of optical storage device and molecular switches.